Efektivitas Metode Enhanced Milieu Teaching (EMT) terhadap Peningkatan Kosa Kata pada Kasus Autism Spectrum Disorders (ASD) - Enita Linggar Aswari; Dian Atnantomi Wiliyanto; Gunawan, Gunawan (Yayasan Literasi Sains Indonesia, 2025)
Children with autism often have primary difficulties in social interaction, behavior, and communication, particularly in vocabulary acquisition. Enhanced Milieu Teaching (EMT) is one of the naturalistic-based methods aimed at improving language skills within the context of everyday play. This study aims to examine the effectiveness of the EMT method in increasing vocabulary in children with autism. It is an experimental study using a One-group Pretest-Posttest Design with a sample of 8 children with autism, aged 4-5 years, at Keanna Center, South Jakarta. The Receptive Verbal Vocabulary Test (TKV-R), which is valid and reliable in Indonesian, was used as the assessment. The intervention was conducted in 12 sessions, each lasting 45 minutes. There was an increase in 7 out of 8 vocabulary items in children with autism after receiving the EMT intervention. The analysis using the Wilcoxon Signed Rank Test showed an increase in the average score from 21 to 27 with a p-value of 0.018. This finding indicates that the EMT method is proven to be effective in improving vocabulary in children with autism.